2022
DOI: 10.3390/ijms231810284
|View full text |Cite
|
Sign up to set email alerts
|

Marine Compounds for Melanoma Treatment and Prevention

Abstract: Melanoma is considered a multifactorial disease etiologically divided into melanomas related to sun exposure and those that are not, but also based on their mutational signatures, anatomic site, and epidemiology. The incidence of melanoma skin cancer has been increasing over the past decades with 132,000 cases occurring globally each year. Marine organisms have been shown to be an excellent source of natural compounds with possible bioactivities for human health applications. In this review, we report marine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…MariClus, therefore, links the predicted compounds produced by marine species to their PubChem page where additional information concerning biochemical pathways, assays, studies and patents can be found. For example, the marine natural product salinosporamide A was discovered in 2003 from marine Salinispora species and has since been commercialized as the proteasome-inhibiting anticancer drug Marizomib [ 36 , 37 ]. Consequently, many papers and patent applications have been published.…”
Section: Resultsmentioning
confidence: 99%
“…MariClus, therefore, links the predicted compounds produced by marine species to their PubChem page where additional information concerning biochemical pathways, assays, studies and patents can be found. For example, the marine natural product salinosporamide A was discovered in 2003 from marine Salinispora species and has since been commercialized as the proteasome-inhibiting anticancer drug Marizomib [ 36 , 37 ]. Consequently, many papers and patent applications have been published.…”
Section: Resultsmentioning
confidence: 99%
“…The marine world represents an endless and varied source of new drugs that can be used to target different diseases, including cancer, immune-and inflammatory-based diseases [7,36]. Multiple data reported that marine compounds from micro-and macro-organisms showed promising in vitro and in vivo activities against melanoma [37]. Among these, Salinosporamide A (under the commercial name of Marizomib), a marine bacterium of the genus Salinospora, has been demonstrated to impair cells growth in multiple human melanoma cell lines at different aggressive stages [38].…”
Section: Discussionmentioning
confidence: 99%